2021
DOI: 10.20344/amp.12562
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Junior Doctors: The Case of Psychiatric Trainees in Portugal

Abstract: Introduction: In the last few decades, the rates of international medical migration have continuously risen. In Psychiatry, there is great disparity in the workforce between high and low-income countries. Yet, little is known about the 'push' and 'pull' factors and the migratory intentions of trainees. This study aims to assess the factors impacting the decisions of psychiatric trainees in Portugal towards migration. Material and Methods: A questionnaire was developed in the Brain Drain study and was distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Consistent with our ndings, a study by Da Costa et al in Portugal indicates that nearly 75% of medical trainees had ever considered leaving the country, while the majority (70%), had not taken any practical steps toward migration (24). On the other hand, a survey of Romanian medical students revealed that 84.4% of the students had planned to work outside Romania (25).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with our ndings, a study by Da Costa et al in Portugal indicates that nearly 75% of medical trainees had ever considered leaving the country, while the majority (70%), had not taken any practical steps toward migration (24). On the other hand, a survey of Romanian medical students revealed that 84.4% of the students had planned to work outside Romania (25).…”
Section: Discussionsupporting
confidence: 89%
“…Other factors, including sociocultural, educational, academic, and personal causes were followed. Financial and occupational factors have been highlighted as the main reasons for healthcare workers' migration in several other studies as well (24,(33)(34)(35). However, in another study on Iranian psychiatric trainees and early-career psychiatrists, political conditions and then work-related factors were considered as the most critical factors affecting the migration of physicians (15).…”
Section: Discussionmentioning
confidence: 97%
“…The findings of this study in Portugal, a country with a similar number of participants (n = 107) and male/female proportion, showed that 75% of respondents had considered migration, and the main reason to consider leaving was financial; the majority of Portuguese respondents showed dissatisfaction with their current salary, working conditions, and academic opportunities. 21…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…The so‐called "brain drain" of medical professionals from lower‐income to higher‐income countries continues the trend of recent years, which has led to vast inequalities in terms of educational budget spending at the level of the origin/donor country, and a subsequent chronic lack of adequate healthcare provision in some of the more underfunded and deprived countries (Oladeji & Gureje, 2016; Pinto da Costa et al, 2017; Pinto da Costa, Giurgiuca, et al, 2019). Examples of the massive toll associated with the "brain drain" of psychiatric professionals on the mental health care services of lower‐income donor countries are not singular, as they range from south‐western (Pinto da Costa, Moreira, et al, 2019) to central and eastern European countries (Matutyte et al, 2020), alongside non‐EU countries, such as Turkey, where a staggering percentage of 75% of psychiatric trainees were considering living and working abroad (Kilic et al, 2018), and several south Asian countries (Patel, 2007; WHO, 2019).…”
Section: Postgraduate Training In Psychiatrymentioning
confidence: 99%